ISLAM NUSANTARA: MANIFESTASI ISLAM ADAPTIF DAN REALITAS BUDAYA ISLAM- MELAYU BENGKULU - Samsudin Samsudin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
Islam Nusantara is the stu dy of the values of Islam are growing and struggling and rooted in the culture of thearchipelago. Islamic dialectics with social reality presents a heterogeneous culture berislam patterns typical and adaptive to change jaman.Akulturasi Islam with cultural heritage, especially the Malay Bengkulu bore patterns of Islamic-Malay culture Bengkulu, for example religious ceremonies, life cycle ceremonies, and ceremonial activities hidup. Kon¬ perceptions customs ‘customary law bersendikan Personality’, Personality ‘bersendikanreligion’ Islam as the supreme judge in view of Malay culture.